Dry vs. wet ad libitum feeding of finishing swine - Vargas Vargas, J.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred finishing pigs were used to evaluate wet vs. dryad libitum feeding. Growth rate of finishing pigs was significantly improved (5%) by wet feeding. Feed utilization was improved 4.5% by wet feeding. Dry feeder type did not influence performance, since all pigs fed dry diets performed similarly. Likewise, pigs fed wet diets performed equally regardless of wet feeder type.
Keywords: Swine; Wet vs. dry ad libitum; Finishing pigs; Growth rate